Criminal Liability of Online Gambling Perpetrators in Indonesia According to the Electronic Information and Transactions Law - Sherly Bantu; Wira Franciska; Hedwig Adianto Mau (Riviera Publishing, 2024)
Online gambling has become increasingly prevalent over a long time due to the ease of access and the ability to play from anywhere with an online association. The reason for this consideration is to look at and analyze the legal provisions against online gambling offenders in Indonesia. The research method used in this study can be a normative legal approach supported by experimental law with graphic depiction. In extension, important information is also used as supporting material for additional information. For control checks, legitimate and standardized check strategies are used. From the search results regarding the legal provisions against the perpetrators of online betting violations in Indonesia, it appears that the legal authority against online betting violations is the criminal sanction against online betting based on Article 45 of Law Number 11 of 2008 concerning Electronic Information and Transactions, but the punishment for the perpetrators is lower than the threat of criminal sanctions in Article 303 of the Criminal Code, so it does not have an inhibiting impact on the perpetrators of online betting violations. Criminal liability for online betting offenses in Indonesia is the responsibility of the perpetrators of online betting offenses indicated by the existence of criminal offense components. In addition, the activity component is one of the most important components in criminal liability, because a person cannot be sentenced if he does not commit an act that is classified as an act rejected by the law.